Olivia Johnson: capstone - Johnson, Olivia, artist (Colorado State University. Libraries, 2022)
The artist's statement: I have always known that art, and more importantly, creating would work its way into my career. I was just unsure of how it would manifest. That is until I toured CSU’s campus and discovered the school’s art program. I walked through the halls of the visual art building looking at all the student work plastered on any and every wall possible, viewing pieces from graphic design classes, photography classes, and fibers classes, and felt a type of inspiration I had never yet felt. I knew at that moment that was where I belonged. Over the years I have found a love for designing packaging, brand identity, marketing materials, and pop-culture-related pieces. Through my exploration of various media over the years, I have settled into designing exclusively digital works. I love the flexibility that digital art lends the maker and allows more experimentation than I ever thought possible. Graphic design makes sense to me in a way that other disciplines such as painting, pottery, and metalsmithing do not. I enjoy working on projects with a clear problem, yet not so clear solution. Working on projects like product packaging, branding, and marketing materials lent to an increased interest in digital marketing, and thus sparked an idea to dive deeper into digital marketing than ever before. I have found a love for the process of working with an individual or brand to create pieces that represent exactly what they want to convey, in a way that they may have never even imagined. Working with a client from a project’s ideation to completion has taught me how to seamlessly blend text, images, and elements to create a piece that encapsulates all that the client needs to communicate in an aesthetically pleasing final product. The projects that I have worked on in various classes have taught me how to design something beautiful while adhering to specific, and sometimes almost impossible parameters.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design